Maybe, my baby - Janovitz, Marilyn (New York : North-South Books, 2003)
Different animal parents try various methods to put their babies to sleep.
"A Cheshire Studio Book."
Keywords: Parental behavior in animals -- Fiction; Animals -- Infancy -- Fiction; Parent and child -- Fiction; Sleep -- Fiction